Pengaruh Perhatian Orang Tua Dan Motivasi Belajar Terhadap Prestasi Belajar Siswa Kelas Atas Sd Negeri 01 Suruh Tahun Ajaran 2015/2016 - VERDIANA, RIZCHA; , Minsih S. Ag, M. Pd (2016)
Rizcha Verdiana/ A510120246. The Ifluence of Parental Attention and Learning Motivation Toward Learning Outcomes of Students Upscale SD N 01 Suruh, told the school year 2015/2016. The Study Program of Education Primary School Teachers, Teachers Training and Education Science Faculty, Muhammadiyah University of Surakarta. April, 2016. This study aims to find out is there is an influence of parent's attention and learning motivation toward to the student learning achievement of upscale. This research is a quantitative model using survey model. The population of this research is an students of SD N 01 Suruh. The sampling technique is Random Sampling, so the sample of this research consisted of 35 students. The conclusion of there is apositive and significant. relationship both parents' attention and learning motivation toward to student learning achievementthrough the correlation coefficirnt coefficient of r "hitung" 0,636. Even t "hitung" is bigger than t "tabel" with the parents attention 2,600> 2,035 while learning motivation 2,701> 2,035. The result showed tht H0 is refused and Ha is related with the parents' attention and learning motivation toward's to the student learning achievement SD N 01 Suruh year 2015/2016. The Data collection techniques is questionnaires and documentation techniques. The test instrument includes validity and reliability test. The data analysis techniques, are uji-t uji-f, multiple regression, R square and predictor donations. It is begin with analysis prequisi test, such as normality test and linerity test.